TNF-Alpha as an Initiator of Allodynia and Anxiety-Like Behaviors in a Preclinical Model of PTSD and Comorbid Pain - Dib, Patrick; Zhang, Yong; Ihnat, Michael A.; Gallucci, Randle M.; Standifer, Kelly M. (Frontiers in Psychiatry, 2021)
Post-Traumatic Stress Disorder (PTSD) is a debilitating mental health disorder that occurs after exposure to a traumatic event. Patients with comorbid chronic pain experience affective distress, worse quality of life, and poorer responses to treatments for pain or PTSD than those with either condition alone. FDA-approved PTSD treatments are often ineffective analgesics, requiring additional drugs to treat co-morbid symptoms. Therefore, development of new treatment strategies necessitate a better understanding of the pathophysiology of PTSD and comorbid pain. The single prolonged stress (SPS) model of PTSD induces the development of persistent mechanical allodynia and thermal hyperalgesia. Increased Nociceptin/Orphanin FQ (N/OFQ) levels in serum and CSF accompany these exaggerated nociceptive responses, as well as increased serum levels of the pro-inflammatory cytokine tumor necrosis factor (TNF-α). Therefore, the primary goal was to determine the role of TNF-α in the development of SPS-induced allodynia/hyperalgesia and elevated serum and CNS N/OFQ using two approaches: TNF-α synthesis inhibition, and blockade with anti-TNF-α antibody that acts primarily in the periphery. Administration of TNF-α synthesis blocker, thalidomide (THL), immediately after SPS prevented increased TNF-α and development of allodynia and hyperalgesia. The THL effect lasted at least 21 days, well after thalidomide treatment ended (day 5). THL also prevented SPS-induced increases in serum N/OFQ and reversed regional N/OFQ mRNA expression changes in the CNS. Serum TNF-α increases detected at 4 and 24 h post SPS were not accompanied by blood brain barrier disruption. A single injection of anti-TNF-α antibody to male and female rats during the SPS procedure prevented the development of allodynia, hyperalgesia, and elevated serum N/OFQ, and reduced SPS-induced anxiety-like behaviors in males. Anti-TNFα treatment also blocked development of SPS-induced allodynia in females, and blocked increased hypothalamic N/OFQ in males and females. This suggests that a peripheral TNF-α surge is necessary for the initiation of allodynia associated with SPS, as well as the altered central and peripheral N/OFQ that maintains nociceptive sensitivity. Therefore, early alleviation of TNF-α provides new therapeutic options for investigation as future PTSD and co-morbid pain treatments.